On the quest for novel bio-degradable plastics for agricultural field mulching - Dar, Sami Ullah; Wu, Zizhao; Zhang, Linyi; Yu, Peirong; Qin, Yiheng; Shen, Yezi; Zou, Yunfan; Poh, Leslie; Eichen, Yoav; Achmon, Yigal (Frontiers in Bioengineering and Biotechnology, 2022)
Plasticulture, the practice of using plastic materials in agricultural applications, consumes about 6.7 million tons of plastics every year, which is about 2% of the overall global plastics production. For different reasons, plastic material used for agriculture is difficult to recycle. Therefore, most of it is either buried in fertile soils, thereby significantly deteriorating their properties, or, at best case, end in landfills where its half-life is measured in decades and even centuries. Hence, biodegradable plastic materials that are suitable for agricultural applications are a vital and inevitable need for the global human society. In our labs, two types of potentially biodegradable plastic-polymer films were prepared and characterized in terms of their biodegradability. In the first approach, polymers made of ionic liquid monomers were prepared using photo radical induced polymerization of ionic liquid monomers. The second approach relies on formation of polyethylene-like n-alkane disulfide polymers from 1,omega-di-thiols through thermally activated air oxidation. These two families of materials were tested for their biodegradability in soils by using a system that combines a controlled environment chamber equipped with a respirometer and a PTR-TOF-MS system. This system provides a time-dependent and comprehensive volatile fingerprint of the degradation process. The results obtained thus far indicate that while the ionic-liquid based polymer did not show significant bio-degradability under the test conditions, the building block monomer, 1,10-n-decane-dithiol, as well as its disulfide-based polymer, are bio-degradable. The latter reaching, under basic soil conditions and room temperature, ~20% degradation within three months. These results suggest that by introduction of disulfide groups into the polyethylene backbone one may be able to render it biodegradable, thus considerably shortening its half-life in soils. Principal component analysis, PCA, of the data about the total volatiles produced during the soil degradation indicates a distinctive volatile “fingerprint” of the disulfide-based bio-degradable products which are from the volatile organic compounds portfolio as recorded by the PTR-TOF-MS. The biodegradation volatile fingerprint of this kind of film was different from the “fingerprint” of the soil background which served as a control. These results can help us to better understand and design biodegradable films for agricultural mulching practices.